Diffusion-Weighted Imaging (DWI) and Diffusion Tensor Imaging (DTI) in Diagnosis of White Matter Diseases of the Brain - Dkhail, Asmaa Hamdy; Younes, Rasha Lotfy; Abdelrahaman Fayed, Hazem; Haroun Emam, Haytham; Dawoud, Mohamed Fathy (Journal of Neonatal Surgery, 2025)
Background: Many White matter diseases involve a diverse range of disorders, either due to improper myelin formation or the loss of previously acquired myelin, with the underlying causes of several of these diseases still being not well understood. This study sought to establish the diagnostic advantage provided by diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) in the diagnosis of WMD. Methods: The case control study involved 50 patients with ages ranging from 5 to 75 and 30 healthy individuals as controls, all of whom exhibited neurological symptoms, sensory issues, or visual difficulties. Magnetic resonance imaging was conducted on all patients. Results: There was a statistically significant difference between the two groups regarding DWI at a significance level of P < 0.05. In the context of DTI, fractional anisotropy values were found to be substantially lower in cases compared to the control group, with a p-value less than 0.05. Furthermore, the mean diffusivity value was significantly higher in cases than in the control group, with a probability of less than 0.05. Conversely, FA values were significantly lower in the corticospinal tract and corpus callosum tract of diseased individuals compared to disease-free controls (P<0.05). Conclusions: DWI and DTI are non-invasive imaging methods that identify subtle structural tissue alterations not visible on standard MRI scans. Across all white matter conditions examined, a decrease in FA values was observed, accompanied by a rise in MD values relative to the control group